Correction: Individual and community-level determinants of knowledge of obstetric danger signs among women in Southern Ethiopia: A multi-level mixed effect negative binomial analysis. - Amanuel Yoseph; Yilkal Simachew; Berhan Tsegaye; Asfaw Borsamo; Yohans Seifu Berego; Mehretu Belayneh (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0314916.].